Retroperitoneal Cecal Perforation Resulting from Obstructive Ascending Colon Adenocarcinoma. (7th January 2020) - Paramythiotis, Daniel; Karakatsanis, Anestis; Moysidis, Moysis; Pagkou, Diamantoula; Bangeas, Petros; Michalopoulos, Antonios
Abstract : Most colorectal cancer patients in the early stages of the disease do not display any alarming symptoms. A total percentage of 9-27% of colorectal cancer patients present with acute abdomen, bowel obstruction, perforation, or bleeding. Perforation as the first presentation of the disease is seen in no more than 2.6-10% of patients. Intestinal perforation may be found on either the site of the tumor or on a more proximal site, caused by distention of the bowel due to peripheral obstruction. This is a case of a 75-year-old female patient who presents in the emergency department with retroperitoneal cecal perforation due to an obstructing tumor of the ascending colon. She underwent an emergency right hemicolectomy and washout of the retroperitoneal space. The cecum is not an unusual site of distention and subsequent perforation in the case of colonic obstruction, especially in the presence of a competent ileocecal valve. While the mechanism of diastatic cecal perforation is well described, it is the first time in the literature that this does not occur on the anterior surface of the organ. In our case, cecal perforation presents as a retroperitoneal abscess without peritoneal spillage. Nonetheless, it still carries a grim prognosis and urgent surgical intervention is needed.